2019
DOI: 10.3390/ma12091484
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Direct Laser Interference Patterning of Aluminum for Fabrication of Super Hydrophobic Surfaces

Abstract: This work addresses the fabrication of hydrophobic surface structures by means of direct laser interference patterning using an optical setup optimized for high throughput processing. The developed optical assembly is used to shape the laser beam intensity as well as to obtain the two sub beams required for creating the interference pattern. The resulting beam profile consists of an elongated rectangular laser spot with 5.0 mm × 0.1 mm size, which enables the optimized utilization of the laser fluence availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…This results in more molten material, forming larger melt fronts and deeper line‐like structures. [ 37,45–48 ] For small spatial periods, it has been already reported that the temperature difference between interference maxima and minima is low, which causes a melting at both positions when high pulse energies or high pulse overlaps are used. Consequently, a loss of structure depth occurs after some number of pulses due to remelting, whereby the homogeneity of the line‐like patterns is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…This results in more molten material, forming larger melt fronts and deeper line‐like structures. [ 37,45–48 ] For small spatial periods, it has been already reported that the temperature difference between interference maxima and minima is low, which causes a melting at both positions when high pulse energies or high pulse overlaps are used. Consequently, a loss of structure depth occurs after some number of pulses due to remelting, whereby the homogeneity of the line‐like patterns is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…For overlaps ranging from 40% to 85% as well as hatches between 40% and 85%, the lowest Z sm /Z fm ratios were obtained (down to~0.3). For overlaps and hatches above 85% the structure becomes inhomogeneous due to the high applied energy leading to a significant deterioration of the pattern uniformity as discussed elsewhere [46].…”
Section: Of 16mentioning
confidence: 91%
“…Thus, the higher thermal conductivity of Scalmalloy ® leads to a larger volume of material that is molten at the interference maxima positions which contributes to the formation of the periodic structure. Furthermore, in case of DLIP treatment with ns pulses, the contribution of the molten material on the structure formation has already been discussed, driven mainly by Marangoni flow and recoil pressure for low and high intensity levels, respectively [ 47 , 48 ].…”
Section: Surface Modification By Dlip Techniquementioning
confidence: 99%